THE FUNCTIONS OF SEKOLAH TIJNAS BAKTI AS REHABILITATION INSTITUTION FROM THE PERCEPTIONS OF STUDENTS (A CASE STUDY IN SEKOLAH TUNAS BAKTI KUCHING) - LIM, KOK MENG (Universiti malaysia sarawak (UNIMAS), 1997)
Based on the humanitarian principles, this study was carried out to determine the perceptions of students of Sekolah Tunas Bakti Kuching towards the implied functions of rehabilitation. The scope of the study was students' perceptions towards four specific major fields of rehabilitation stated in programmes of Sekolah Tunas Bakti Kuching. The four fields are (i) educational and vocational programmes; (ii) privilege and grading system; (iii) counselling; and (iv) religious teaching. The research findings show that students have a more positive perception than negative perception toward the four fields of rehabilitation. The rank order of positive perception of students, based on each mean score accumulated was: religious teaching, educational and vocational programmes, counselling, privilege and grading system. From the students own perception of their self-improvement, the data show that 94.9% of them noted a positive change since their detention in Sekolah Tunas Bakti Kuching. However, there is only a weak correlation (P:::::O.099) between the two variables of their perception of their self-improvement and their perception of the functions of rehabilitation of Sekolah Tunas Bakti Kuching.